Fluid-rock interaction recorded in black fault rocks in the Kodiak accretionary complex, Alaska - Asuka, Yamaguchi; Tsuyoshi, Ishikawa; Yasuhiro, Kato; Tatsuo, Nozaki; Christie, D. Rowe; James, Casey Moore; Akito, Tsutsumi; Gaku, Kimura; MENEGHINI, FRANCESCA (Earth, Planets and Space, 2014)
Ultrafine-grained black fault rocks (BFRs) in the Pasagshak Point Thrust of the Kodiak accretionary complex are examples of fault rocks that have recorded seismicity along an ancient subduction plate boundary. Trace element concentrations and 87Sr/86Sr ratios of BFRs and surrounding foliated/non-foliated cataclasites were measured to explore the nature of fluid-rock interactions along a subduction thrust. Foliated and non-foliated cataclasites do not show significant geochemical anomalies, suggesting that they were formed by slowly distributed shear. BFRs are characterized by Li and Sr enrichment, Rb and Cs depletion, and a low 87Sr/86Sr ratio. These geochemical signatures can be explained by fluid-rock interactions at >350°C, which result in preferential removal of Rb and Cs and formation of plagioclase under the presence of fluids with high Li and Sr concentrations and low 87Sr/86Sr ratios. Geochemical anomalies recorded by the BFRs indicate both frictional heating and external fluid influx into the subduction thrust.